Exploring the mesophase and optical behavior of novel furan-based chalcone liquid crystals with ester/azo linkages - Sezgin, Baris; Karanlik, Ceren Can; Karanlik, Gurkan (ROYAL SOC CHEMISTRY, 2025)
We report the synthesis, structural and mesomorphic characterization of two novel furan-based thermotropic calamitic liquid crystals bearing chalcone-based central cores. The designed molecules CEE (chalcone/ester/ester) and CEA (chalcone/ester/azo) differ by their linking groups and are functionalized with a polar bromine substituent at one terminal and a flexible n-dodecyloxy chain at the other. Structural characterization was carried out using NMR spectroscopy and elemental analysis technique and mesomorphic properties were investigated via polarized optical microscopy (POM) and differential scanning calorimetry (DSC). The thermal stability of the compounds was determined by thermogravimetric analysis (TGA). Both compounds exhibit enantiotropic smectic A phases; notably, CEA also displays a monotropic nematic phase during cooling. Photoisomerization studies of CEA revealed efficient trans-cis isomerization under UV irradiation, indicating its photoswitching capabilities. Furthermore, Density Functional Theory (DFT) calculations were conducted to evaluate the electronic structure and nonlinear optical (NLO) properties of the compounds. Compared to the reference molecule urea, both CEE and especially CEA exhibit significantly enhanced dipole moments, polarizability, and first hyperpolarizability (beta tot) establishing CEA as a promising candidate for photonic and optoelectronic applications. This study highlights the critical role of molecular design and linker variation in tuning mesomorphic and optical properties of liquid crystalline materials.
Keywords: POLAR ORDER; DERIVATIVES; AZOBENZENE; PROPERTY; Chemistry